About conceptual apparatus in the field of administration in the court system - Дудченко, О. Ю. (Theory and practice of jurisprudence, 2016)
The different going near determination of concepts that are used in administrative relations into the court system is researched , the sense of concepts «judicial management», «organizational management by the courts», «organizational provision of the court activity» are considered in the article. The legal essences of the investigated concepts are analyzed and author’s opinion about its meaning and application is reported